Misuse of Aspirin and Associated Factors for the Primary Prevention of Cardiovascular Disease - Chen, Yinong; Yin, Chun; Li, Qing; Yu, Luyao; Zhu, Longyang; Hu, Dayi; Sun, Yihong (Frontiers in Cardiovascular Medicine, 2021)
Background: The value of aspirin for primary prevention continues to be debated. Data showing whether aspirin use for primary prevention adheres to established guidelines in real world practice are sparse. Methods: A total of 13,104 patients without cardiovascular diseases (CVD) were selected from the DYS-lipidemia International Study of China, a national survey of patients with dyslipidemia in 2012. The CVD risk of the participants were calculated using the 10-year risk of Ischemic Cardiovascular Diseases model. The overuse of aspirin for primary prevention was defined as having CVD risk <10% with daily aspirin. Multivariate logistic regression models were used to explore risk factors associated with aspirin overuse. Results: The proportion of the patients categorized as low, moderate and high risk for CVD were 52.9%, 21.6%, and 25.4% respectively. The overuse frequency of aspirin was 31.0% (2,147/6933) in patients with low risk. The overuse of aspirin increased with ageing for both men and women. In the multivariate analysis, the independent risk factors associated with aspirin overuse were hypertension, diabetes mellitus, a family history of premature CVD, and elderly age. Level of total cholesterol is negatively associated with aspirin overuse. Patients from low level hospitals are more likely to be taking aspirin inappropriately. Results remained consistent after including 2837 patients having 10-year risk for CVD between 10% to <20%. Conclusion: The overuse of aspirin for primary prevention is common in patients having CVD risk <10%. There are important opportunities to improve evidence-based aspirin use for the primary prevention of CVD in Chinese patients. Clinical Trial Registration: https://clinicaltrials.gov/, identifier: NCT01732952. Key words: aspirin, primary prevention, cardiovascular disease, overuse, risk factors